PENYULUHAN HUKUM SEBAGAI UPAYA MAHASISWA FAKULTAS HUKUM UBHARA JAYA AGAR TERHINDAR DARI HUMAN SECURITY DI DESA SRIAMUR TAMBUN UTARA BEKASI - Amalia Syauket (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Sriamur Tambun Utara Bekasi Village, which is ourpartner in the location of the real work college, is one of thevillages with the status of an advanced village. So, governance isgood. However, geographically, Sriamur Village, which isincluded in the Bekasi Regency Region, is a buffer zone to theCity of Jakarta with the characteristics of an industrial area thatis closely related to labor issues, low public education under thenational human development index, which has an impact on thenumber of early marriages, rampant domestic violence, victimsof online loans and human trafficking. Besides that, the otherimpact is the high level of brawls and narcotics abuse among theyounger generation, all of which are daily threats faced by thepeople of Sriamur Village in their lives. The real work lectureprogram for UBJ Faculty of Law students has been going on forone month at the end of 2022 the 2022/2023 academic year bycarrying out physical and non-physical activity programs as aneffort to avoid human security with a community satisfactionlevel above 90%..